Caracterização dos empreendimentos e perfil dos empreendedores no centro comercial do município de Grossos-RN - Oliveira, Kelvin Henrique Martins de (Universidade Federal Rural do Semi-Árido, 2020)
Entrepreneurship can be defined as an act of entrepreneurship, that is, creating, innovating, launching and meeting people's needs through products for greater satisfaction and well-being. With this, the present work has as general objective, to characterize the profile of entrepreneurs in the municipality of Grossos of the State of Rio Grande do Norte, to diagnose and characterize the profile of enterprises and entrepreneurs and thereby understand the commercial scenario of the municipality. Given the methodology used for research, it was done through a descriptive research, made through a bibliographic review and data collected in the field research, where it was characterized according to its nature in a quantitative research. Obtaining data and information about local entrepreneurs may result in obtaining resources for the evolution of the enterprises, making local trade sustainable. Responding to the objective of the work, the distribution by gender has a predominance of men, but women have been gaining strength and inserting themselves in the commercial environment of the municipality, but with the presence of women gradually entering the labor market. With commerce based on trade in supplies and services, there is a shortage of some types of ventures or options to choose from, such as steakhouses, electronics stores, opticians, etc. Finally, entrepreneurs in the municipality of Grossos seek to develop their business more and more through new ideas and based on people's needs, without losing focus on future economic interests and positive results.
Monografia
Keywords: Empreendedorismo; Comércio; Negócios; Serviços; Entrepreneurship; Trade; Business; Services; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA